Determination of Entrepreneurial Knowledge and Locus of Control Through The Family Environment In The Interest of Entrepreneurship Students STMB MULTI SMART Medan - Hidayat, Ferry; Angelyn Veronica (International Journal of Economics (IJEC), 2022)
This study aims to examine the interest in entrepreneurship, which is determined by entrepreneurial knowledge, family environment, and locus of control in STMB MULTISMART students in the development of entrepreneurial learning patterns that are very important to do because each college has different characteristics of students. The causal associative research approach was conducted through descriptive quantitative techniques with a population of 74 people and the entire population sampled. The research instrument used a questionnaire with a Likert scale. The data analysis technique used in this study is the Partial Least Square (PLS) method, assisted by SmartPLS 3 software. Based on the results of the study, which showed no effect of entrepreneurial knowledge on entrepreneurial interest; there is a positive and significant influence of locus of control on the interest of entrepreneurship; there is a positive and significant influence of the family environment on the interest in entrepreneurship; there is a positive and significant influence of entrepreneurial knowledge on the interest in entrepreneurship through the family environment; and there is a positive and significant influence of locus of control on the interest in entrepreneurship through the family environment. A more realistic approach to teaching entrepreneurship courses is needed by prioritizing practice, such as testing the manufacture of products that have differences from similar products and trying new ideas in a service. In addition, students need to be included in entrepreneurship competitions at local and national levels. This is certainly intended for students to get empirical learning.